Farming and cropping systems in the West African Sudanian Savanna. WASCAL research area: Northern Ghana, Southwest Burkina Faso and Northern Benin - Daniel Callo-Concha; Thomas Gaiser; Frank Ewert (University of Bonn, Center for Development Research (ZEF), 2012)
Ecological fragility combined with institutional weakness and political and economic instability make West Africa one of the most vulnerable regions to climate change. The West African Science Service Center on Climate Change and Adapted Land Use (WASCAL) tackles this vulnerability by investigating the interface of climate and rural socia-ecological systems, in order to propose ad hoc adaptation measures. In this context, the characterization of the livelihoods of rural communities is crucial since these constitute the units of evaluation and analysis of ongoing and forthcoming studies. Purposefully, this paper provides a joint description of these livelihoods. Divided in three sections, the first one focuses on the agroecological (biophysical) characteristics, detailing climatic, edaphological and hydrological qualities mainly; the second section, portrays the principal socioeconomic features: demography, culture, and organizational and economic institutions; and the third section, describes the main farming and cropping systems themselves, matching the first sections outcomes with managerial aspects, such as farming practices and regional variations, planting patterns, etc. The paper concludes with an overview on relevant features of the farming and cropping systems, recalling the main limiting factors and the local strategies used to overcome them.
Keywords: 330; climate change; West Africa; cropping systems; farming systems; vulnerability